Papers from the 33rd Conference of the Southeast Asian Linguistics Society (2024) - Alves, Mark (Journal of the Southeast Asian Linguistics Society)
This is the thirteenth JSEALS Special Publication. The goal of JSEALS Special Publications is to share collections of linguistics articles, such as select papers from conferences or other special academic events, as well as to offer a way for linguistic researchers in the greater Southeast Asian region to publish monograph-length works. This publication contains papers of talks given at the 33rd annual meeting of the Southeast Asian Linguistics Society. SEALS 33 was hosted by Tsinghua University in Taipei, Taiwan under the guidance of Dr. Hsiu-chuan Liao from the 15th to the 17th of May in 2024. Dr. Liao also arranged a special workshop on the 18th after SEALS entitled “Workshop on Southeast Asian Linguistics: Language Contact and Historical Relationships of Languages in Southeast Asia”, at which several specialists in the field gave talks. This volume contains nineteen articles: ten on morpho-syntactic matters, three on phonology, five on historical linguistics, and one on sociolinguistics. The languages covered in this volume are spoken throughout the greater Southeast Asian region, including both Mainland and Insular Southeast Asia (and Taiwan), bordering areas of southern China, and the Indian Subcontinent. The studies cover the five main language families in the region: Austronesian, Austroasiatic, Hmong-Mien, Kra-Dai, and Sino-Tibetan/Trans-Himalayan. We are very pleased that JSEALS is able to support SEALS and to contribute to the sharing of quality linguistic research in Greater Southeast Asia. We look forward to being able to produce such works for SEALS in the future.